Calcium carbonate and ammonium polyphosphate flame retardant additives formulated to protect ethylene vinyl acetate copolymer against fire: Hydrated or carbonated calcium?. Issue 2 (31st August 2020) - Laoutid, Fouad; Vahabi, Henri; Movahedifar, Elnaz; Laheurte, Pascal; Vagner, Christelle; Cochez, Marianne; Brison, Loïc; Saeb, Mohammad Reza
Abstract: In this study, the effect of the chemical nature of different calcium (Ca)‐based minerals as flame retardant additives in combination with ammonium polyphosphate (APP), in 1:1 proportions, on the flame retardancy behavior and performance of ethylene vinyl acetate copolymer was discussed. Combining APP with partly and completely hydrated calcium oxide led to superior flame‐retardant function detected in mass loss calorimeter measurements with respect to the corresponding system containing carbonated calcium. This privileged character was attributed to the higher reactivity of hydrated Ca‐based fillers toward APP in comparison with Ca carbonate, which induced the formation of an intumescent residue. The difference between reactivity potential of hydrated and dry Ca was demonstrated by the newly formed thermally stable species, and further evidenced by thermogravimetric analysis performed on APP/fillers blends. Moreover, the presence of more crystalline domains in the Ca/phosphorus‐based compounds was evidenced by XRD analysis of the mass loss calorimeter test residues. The results of this work highlight the role of blend additive systems on the performance of flame retardancy of polymer materials. Abstract :